Association between the Use of Antibiotics and the Development of Acute Renal Injury in Patients Hospitalized for COVID-19 in a Hospital in the Peruvian Amazon - Romaní, Luccio (2022)
“Introduction: A significant antibiotic prescribing pattern associated with the COVID-19 pandemic has been described. Multiple protocols included empirical antimicrobials, leading to a substantial increase in antimicrobial consumption in medical care. A higher mortality rate is described among patients diagnosed with COVID-19 who received antibiotics. Objectives: To determine the association between the use of antibiotics and the development of acute renal injury in patients infected with SARS-CoV-2 in patients treated at the Hospital II EsSalud de Ucayali, 2021. Methods: A cross-sectionalanalytical study was conducted, evaluating the medical records of patients admitted to the intensive care unit between July 2020 and July 2021. For the statistical analysis, measures of central tendency and dispersion, statistical hypothesis contrast tests were used in relation to acute kidney injury (AKI), antibiotic use and associated factors, derived from linear regression models. Results: The factors that were positively associated with the development of AKI were sepsis (aPR: 2.86; 95% CI: 1.26–6.43), shock (aPR:2.49; 95% CI: 1.28–4.86), mechanical ventilation (aPR:9.11; 95% CI: 1.23–67.57), and use of vancomycin (aPR: 3.15; 95% CI: 1.19–8.27). Conclusions: In the Peruvian Amazon, there is a high consumption and inadequate prescription of antibiotics. The drugs most commonly used for the treatment of COVID-19 were: aminoglycosides, vancomycin, ivermectin, azithromycin, tocilizumab, and corticosteroids. The development of AKI among hospitalized patients was found to be related to vancomycin administration. In addition, an association was found with the use of mechanical ventilation, a high body mass index, and the presence of complications such as sepsis or shock. Therefore, inappropriate antibiotic use for COVID-19 has been associated with multiple negative outcomes and consequences. “